Practical implications of the updated WHO classification of brain tumors - Martinez-Lage, Maria; Sahm, Felix (Seminars in neurology, 2018)
The updated 2016 WHO classification of Central Nervous System tumors introduced a novel concept of neuropathology diagnostics. Molecular parameters are now included into the definition of several entities. This evolution from a previously purely histology-based classification to an integrated approach of histology and genetic characteristics has implications in daily diagnostic and clinical practice. Both the spectrum of diagnostic workup demanded from the neuropathologist and the range of relevant markers to be considered by clinicians and clinical investigators have increased. This article reviews the major changes in the classification of diffuse gliomas, ependymoma, and medulloblastoma, the practical consequences for diagnostics and clinical trials, and points toward recent developments that potentially will influence the next update of the classification.